The rise of big data in disease ecology. Issue 12 (December 2021) - Doherty, Jean-François; Chai, Xuhong; Cope, Laurie E.; de Angeli Dutra, Daniela; Milotic, Marin; Ni, Steven; Park, Eunji; Filion, Antoine
Abstract : Big data have become readily available to explore patterns in large-scale disease ecology. However, the rate at which these public databases are exploited remains unknown. We highlight trends in big data usage in disease ecology during the past decade and encourage researchers to integrate big data into their study framework.